Answer:
Recursive formula is
![a_n = (a_(n-1) *3) + 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/g2abwxuxjhiu9t1f7kyaz24ybt6m598rrd.png)
Explanation:
8, 26, 80, 242, . . .
8 is the first term
To get 26 we multiply 8 by 3 and then add 2
8*3 = 24 + 2= 26
26 * 3= 78+2 = 80
80*3 = 240 + 2 = 242
So to get next term we multiply the previous term by 3 and then we add 2
![a_n = (a_(n-1) *3) + 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/g2abwxuxjhiu9t1f7kyaz24ybt6m598rrd.png)